Clinicopathological Characteristics and Mutation Spectrum of Colorectal Adenocarcinoma With Mucinous Component in a Chinese Cohort: Comparison With Classical Adenocarcinoma - Chen, Jingci; Zhou, Liangrui; Gao, Jie; Lu, Tao; Wang, Jing; Wu, Huanwen; Liang, Zhiyong (Frontiers in Oncology, 2020)
Background: Colorectal adenocarcinoma with mucinous component (AWMC) is a special entity of colorectal cancer. The study is aimed at analyzing the clinicopathological characteristics, molecular mutation spectrum, and prognosis of AWMC and comparing it with classical adenocarcinoma (AC) in a Chinese cohort. Methods: 108 AMWC and 204 AC patients were included. Targeted next-generation sequencing (NGS) was performed on formalin-fixed paraffin-embedded (FFPE) tissues. AWMC was further divided into two groups: AWMC with signet ring cell component and AWMC without signet ring cell component. Clinicopathological features, mismatch repair protein (MMR) status, genetic alterations, and survival outcomes were analyzed after tumor location was taken into consideration. Results: AWMC had larger tumor size (p=0.014) and showed predilection for proximal colon (p<0.001) compared with AC. Regardless of primary sites, AWMC was associated with less metastasis (p<0.001) and earlier AJCC stage (p<0.001). Mismatch repair protein deficiency (dMMR) was more commonly detected in AWMC than in AC for right-sided colon (p<0.001), but the difference was not significant for left-sided colon (p=0.081). The five most commonly mutated genes in AWMC were KRAS (45.4%), TP53 (39.8%), APC (22.2%), PIK3CA (22.2%), and SMAD4 (10.2%). AWMC showed a significantly lower mutation rate of TP53 than AC, both in right-sided colon and in left-sided colon (p<0.001 and p=0.033, respectively). In left-sided colon, AWMC with signet ring cell component had a significantly smaller size than tumors with signet ring cell component (p=0.034). No dMMR cases were detected in AWMC with signet ring cell component (n=7). Moreover, AWMC with signet ring cell component had a significantly lower KRAS mutation rate than AWMC without signet ring cell component, both in right-sided colon and in left-sided colon (p=0.036 and p=0.012, respectively). The disease-specific survival (DSS) for AWMC and AC were not statistically different (p=0.0587). Multivariate analysis showed that AWMC was not an independent predictor of prognosis. Conclusion: Regardless of primary sites, AWMC demonstrates less metastasis, earlier stages, more frequent dMMR, and lower TP53 mutation rate than AC. Our results indicate that different molecular pathogenesis might underlie mucinous morphology in colorectal carcinoma. Mucinous component is not an independent factor of outcome.